2017
DOI: 10.1007/s11655-017-2420-1
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Classification of Enterovirus 71-Associated Hand, Foot, and Mouth Disease in Chinese Medicine: A Retrospective Study in 433 Cases

Abstract: LCA on reported symptoms and signs in a retrospective study allowed different subgroups with meaningful clinical correlates to be defined. These findings provide evidence for targeted prevention and treatment interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Moreover, other study has demonstrated that BNP and PCT levels can be an indicator of severe fatal HFMD. Although the pathogenesis of HFMD has not yet been fully clarified ( 15 ), it is related to the inhibition of immune function, especially cellular inhibition of immune function. Therefore, we conducted a retrospective study to analyze the relationship between the severity of HFMD and cellular immunity, age, and PCT and BNP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other study has demonstrated that BNP and PCT levels can be an indicator of severe fatal HFMD. Although the pathogenesis of HFMD has not yet been fully clarified ( 15 ), it is related to the inhibition of immune function, especially cellular inhibition of immune function. Therefore, we conducted a retrospective study to analyze the relationship between the severity of HFMD and cellular immunity, age, and PCT and BNP levels.…”
Section: Discussionmentioning
confidence: 99%